Mihrab design and its basic acoustical characteristics of traditional vernacular mosques in Malaysia - Ahmad, Y.; Din, N.C.; Othman, R.Y. (Penerbit UKM, 2013)
Mosque design, globally, has evolved considerably from being very simple design and functional, to more sophisticated forms and layout and recently being very monumental. Its function; however,remain the same, not only as a place for prostrations, but more so as a community centre and a symbol of Islam. Basic elements and spaces such as prayer hall, ablution, minaret, minbar and mihrab; for example, are common features in any mosque. Mihrab, a component of Qibla wall marks the Qibla direction. Functionally, it positions the Imam who recites during congregations. It form and design helps the Imam to have khusyu’ in prayer. Mihrab should also function acoustically. This research was carried out with the objectives to review the level of acoustic performance in selected mosques and to evaluate the design and acoustic performance of the mihrabs. Initial survey of 37 traditional mosques in Malaysia, built between 1728-1830, has concluded that the mosques are either square or rectangular in plan with clear Mihrab visibility from the main entrance. Mihrab’s form vary from having circular niche with flat ceiling to rectangular shaped with slanting ceiling and semi-circular concaved niched forms. To evaluate the acoustical characteristics of the selected mosques the PCbased acoustic measuring system and analyser was utilized. The PC-based measuring system (dBBati32) was integrated with sound level meter (01dB Solo Metravib) as analyser. Data collected from five case study reveals initial findings that the operating facilities in the mosques resulting higher rating NC-49 which is reducing the performance of speech intelligibility. The investigations on the mosque’s mihrab offer good characteristics to confirm the tendency of fair acoustical performance with a maximum difference of 4.0dB.